The 1/N expansion of colored tensor models in arbitrary dimension - Gurǎu, Rǎzvan; Rivasseau, Vincent (epl, 2011)
In this paper we extend the 1/N expansion introduced in Gurau R., Ann. Henri Poincaré, 12 (2011) 829, to group field theories in arbitrary dimension and prove that only graphs corresponding to spheres SD contribute to the leading order in the large-N limit.
Gesehen am 30.09.2022